Răspuns :
Răspuns:
Explicație pas cu pas:
x * y = x+y+x²·y²
-------------------
a) 1 * 2 = 1 + 2 + 1²·2² = 3+4 = 7
b) x * e = e * x = x ; e = 0 ?
x * 0 = x+0+x²·0² = x
0 * x = 0+x+0²·x² = x =>
x * 0 = 0 * x = x => e = 0 = element neutru
c) (-2) * x ≤ 3 ; x = ? I x ∈Z
(-2) * x ≤ 3 <=> -2+x+(-2)²·x² ≤ 3 =>
4x²+x-5 ≤ 0
4x²+x-5 = 0 => a = 4 ; b = 1 ; c = -5 ; Δ = b²-4ac = 1-4·4·(-5) = 81
√Δ = √81 = 9
x₁,₂ = (-b±√Δ)/2a = (-1±9)/8
x₁ = -10/8 = -5/4
x₂ = 8/8 = 1
4x²+x-5 ≤ 0 => x ∈ [-5/4 ; 1] I x ∈ Z => x = { -1 ; 0 ; 1}
#copaceibrainly